2012
DOI: 10.1136/bmj.e6603
|View full text |Cite
|
Sign up to set email alerts
|

Plantar fasciitis

Abstract: points• Plantar fasciitis is a condition which generally resolves over time with minimally-invasive management • There is no one treatment with the highest level of evidence, but several with moderate levels of evidence, including stretching, orthotics, shock wave therapy, and injections• The secondary cost of prolonged immobility can be severe (and can also worsen plantar fasciitis), so it is worth treating plantar fasciitis actively rather than with neglect• Choice of treatments should be tailored to the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 30 publications
2
88
0
1
Order By: Relevance
“…It is an enthesopathy that arises from degenerative processes affecting the junction between the periosteal (calcaneus) and the ligament attachment (plantar fascia). (3) Plantar fasciitis can affect both athletes and sedentary people, particularly middle-aged and older individuals. (4) Intrinsic risk factors include obesity, pes planus, pes cavus and a shortened Achilles tendon.…”
Section: Introductionmentioning
confidence: 99%
“…It is an enthesopathy that arises from degenerative processes affecting the junction between the periosteal (calcaneus) and the ligament attachment (plantar fascia). (3) Plantar fasciitis can affect both athletes and sedentary people, particularly middle-aged and older individuals. (4) Intrinsic risk factors include obesity, pes planus, pes cavus and a shortened Achilles tendon.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of flat feet to excessively roll inward during walking or running makes them more susceptible to plantar faciitis. [16][17][18] Obesity is seen in 70% of individuals who present with plantar fasciitis and is an independent risk factor. 19 Studies have suggested a strong association exists between an increased body mass index and the development of plantar fasciitis in the non-athletic population; this association between weight and plantar fasciitis has not been observed in the athletic population.…”
Section: Discussionmentioning
confidence: 99%
“…I) 4 . PF is experienced in both recreational and élite athletes and is reported in different sports 6 . A recent review concerning ankle and foot injuries in sport, has pointed out that Achilles tendinopathy is the most frequently investigated injury, mostly in running and soccer athletes.…”
Section: Plantar Fasciitis In Athletes: Diagnostic and Treatment Stramentioning
confidence: 99%
“…heel cups, insoles and night splints) were used to improve PF symptoms, thanks to the reduction of the pressure on the plantar fascia. Low-dye taping and kinesiotaping are also considered for the treatment of PF 4,6,11 . Noteworthy, the weight loss is the primary treatment for overweight people (Table III) 4,6 .…”
Section: Treatment Of Pfmentioning
confidence: 99%
See 1 more Smart Citation